Nobody feels safe: vulnerability, fear and the micro-politics of ordinary voice in crime news television - Higgins, Kathryn Claire (2021)
The new prominence of ordinary voice in crime journalism – claims to have seen things, experienced things, felt things ‘first-hand’ – has the potential to decenter elite perspectives and open up crime news narratives to the voices of systemically criminalized subjects. However, I argue in this paper that the political potential of ordinary voice can only be realized in and through concrete instances of its use, and so needs to be examined within news texts as sites of micro-political struggle over meaning. Looking at Australian current affairs television coverage of so-called ‘African gang’ crime in Melbourne, this paper approaches crime news texts as sites of vulnerability politics, where different and sometimes competing claims to vulnerability encounter one another and struggle for public recognition. A close multi-modal analysis of three episodes of current affairs television uncovers four specific strategies of textual composition and presentation by which the criminalization of Black African youth is able to persist despite the testimonial interventions of the criminalized: appropriation, marginalization, subjugation and calculation. The paper concludes by considering the implications of this analysis for future studies of ordinary voice and citizen testimony in news reporting